2015
DOI: 10.1038/jhg.2015.39
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the polymorphisms of GSTT1, GSTM1 and methylation of arsenic in the residents exposed to low-level arsenic in drinking water in China

Abstract: We carry out a study to analyze the relation between polymorphisms of GSTT1, GSTM1 and the capacity of arsenic methylation in a human population exposed to arsenic in drinking water. 230 randomly chose subjects were divided into four subgroups based on the arsenic levels, and then the associations between the polymorphisms of GSTT1, GSTM1 and methylation of arsenic were investigated. The levels of inorganic arsenic (iAs), monomethylated arsenic (MMA), dimethylated arsenic (DMA) and total arsenic (TAs) in urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…GSTT1 wild/null polymorphism could have no relevance to urinary As in the populations studied [ 108 , 109 ]. while in other studies individuals who were GSTT1 null had an elevated DMA% in urine [ 110 ], a higher proportion of MMA, a significantly higher PMI and a significantly lower SMI [ 60 , 111 ]. Our results do not confirm previous findings and although GSTT1 could be involved in As metabolism and influence the internal dose of methylated As, its role remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…GSTT1 wild/null polymorphism could have no relevance to urinary As in the populations studied [ 108 , 109 ]. while in other studies individuals who were GSTT1 null had an elevated DMA% in urine [ 110 ], a higher proportion of MMA, a significantly higher PMI and a significantly lower SMI [ 60 , 111 ]. Our results do not confirm previous findings and although GSTT1 could be involved in As metabolism and influence the internal dose of methylated As, its role remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 95%
“…Growing interest has recently focused on the factors influencing As methylation. Besides the As exposure, individual’s ethnicity [ 17 ], age, gender, Body Mass Index (BMI) [ 34 , 47 , 53 ], tobacco smoking [ 54 ], dietary habits [ 55 , 56 ], and inherited genetic characteristics [ 57 , 58 , 59 , 60 , 61 ] were reported to be related to MC.…”
Section: Introductionmentioning
confidence: 99%
“…Its reduced state can donate a reducing equivalent to other molecules, and be involved in the reducing reactions of arsenic methylation ( Kobayashi et al, 2005 ; Waters et al, 2004 ). There is debate on whether SNPs in the GST family are associated with arsenic methylation efficiency ( Kile et al, 2005 ; McCarty et al, 2007 ; Steinmaus et al, 2007 ; Yang et al, 2015 ). One study found that SNPs in GSTT1 and GSTM1 are associated with MMA and DMA levels ( Yang et al, 2015 ), while another study's findings did not support this conclusion ( Kile et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is debate on whether SNPs in the GST family are associated with arsenic methylation efficiency ( Kile et al, 2005 ; McCarty et al, 2007 ; Steinmaus et al, 2007 ; Yang et al, 2015 ). One study found that SNPs in GSTT1 and GSTM1 are associated with MMA and DMA levels ( Yang et al, 2015 ), while another study's findings did not support this conclusion ( Kile et al, 2013 ). There is also no agreement about the SNP-environment interactions of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the researchers found that people with skin lesions and high arsenic exposure are likely to have reduced arsenic methylation capacity with high trivalent species MMA in urine ( 45 48 ). The methylation capacity might reduce with increasing dose of arsenic, smoking and alcohol consumption, age, and nutritional folate deficiency ( 46 , 49 , 50 ). On the contrary, one study from China reported about higher methylation capacity among people above 40 years of age compared to below 40 years, but they also found positive correlation between %MMA and risk of skin lesion.…”
Section: Understanding the Present State Of Researchmentioning
confidence: 99%